Risk Factors and Outcome of Increased Red Blood Cell Transfusion in Cardiac Surgical Patients Aged 65 Years and Older - Isil, Canan Tulay; Yazici, Pinar; Bakir, Ihsan (The Thoracic and Cardiovascular Surgeon, 2015)
Background The use of blood products is not uncommon during cardiac surgery in elderly patients. We conducted this study to investigate the risk factors and adverse outcomes of increased red blood cell (RBC) transfusion in the patients aged ≥ 65 years undergoing cardiac surgery.Methods During 1 year period, 288 patients (197 male/91 female) aged ≥ 65 years who underwent coronary and/or valvular surgery were retrospectively reviewed. Patients were stratified into groups on the basis of the number of transfusions received (< 4 and ≥ 4 U) which was classified as increased transfusion. Univariate analysis and multivariate logistic regression were used to identify risk factors for increased transfusion.Results The mean unit of RBC transfusion was 4.5 ± 3.1 and 55.9% (n = 161) of patients received ≥ 4 U RBC. The overall postoperative complication rate was 36% and significantly higher in those with ≥ 4 U) RBC transfusion (p < 0.01). Risk factors including age, EuroSCORE, and low body surface were significantly higher in patient with ≥ 4 U RBC transfusion. Besides, preoperative anemia, postoperative drainage volume, and fresh frozen plasma (FFP) transfusion during hospital stay were found to be significantly associated with increased transfusion requirements. No difference was observed in mortality (p = 0.13).Conclusion These results suggest that improvement in blood transfusion policy in elderly patients undergoing cardiac surgery requires elimination of preoperative anemia, careful attention to surgical hemostasis, and FFP use.
Keywords: coronary artery bypass graft; elderly; outcomes